2015
DOI: 10.1089/brain.2014.0334
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Changes and Executive and Social Problems in Neurofibromatosis Type I

Abstract: Neurofibromatosis type 1 (NF1) has regularly been associated with cognitive, social, and behavioral problems. The fact that many different cognitive and behavioral impairments have been observed in NF1 suggests that networks of brain regions are involved rather than specific brain regions. Here, we examined whether functional connectivity was different in NF1 and, if so, whether associations were present with cognitive, social, and behavioral outcomes. Fourteen NF1 patients (8 male, age: M = 12.49, SD = 2.65) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 61 publications
(63 reference statements)
3
45
1
Order By: Relevance
“…This result does not allow for causal inference but supports the hypothesis that in addition to the amygdala (Molosh et al ), alterations in PFC in Nf1 +/− mice (and also in NF1 patients) contribute to the social deficits of these mice. This finding is consistent with a recent human study in NF1 patients, suggesting an important role for the frontal cortex in social cognition performance (Loitfelder et al ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result does not allow for causal inference but supports the hypothesis that in addition to the amygdala (Molosh et al ), alterations in PFC in Nf1 +/− mice (and also in NF1 patients) contribute to the social deficits of these mice. This finding is consistent with a recent human study in NF1 patients, suggesting an important role for the frontal cortex in social cognition performance (Loitfelder et al ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, featuring a structure–function correlation approach, we found indications for an important role of the PFC in the social cognition deficits in the Nf1 +/− mouse model. The PFC and CPu were chosen as regions of interest for analyses because previous human studies had already shown impairments in these structures (Cutting et al ; Duarte et al ; Greenwood et al ; Karlsgodt et al ; Loitfelder et al ; Shilyansky et al ,b; Steen et al ; Violante et al ). Despite their correlational (non‐causal) nature, these results are interesting because they point to an important role of high‐level structures such as the PFC in social cognition, in addition to the amygdala (Molosh et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed intra-module clustering pattern suggests that NF1 networks have stronger between-module connectivity and weaker within-module connectivity than controls. These findings are in line with the two prior resting state functional MRI studies of NF1, in which (using seed-based approaches) the investigators find altered short-range connectivity patterns in NF1 participants compared to controls [Chabernaud et al, 2012;Loitfelder et al, 2015]. Together, these data indicate less tightly organized clustering of visual and default mode networks and potentially impaired intramodular affiliation.…”
Section: Discussionsupporting
confidence: 88%
“…Preliminary evidence suggests that resting state (i.e., task-free) BOLD activity patterns in NF1 may be modifiable (e.g., by pharmacological treatment: Chabernaud et al, 2012). Relative to healthy controls, abnormal resting state functional connectivity has also been identified in NF1 (Loitfelder et al, 2015; Tomson et al, 2015). …”
Section: Introductionmentioning
confidence: 99%